Analysis of the Level of Saturation and Fatigue in Offline Learning Academic Year 2022-2023 at ABC Elementary School in Surabaya - Yekti Condro Winursito; Rusindiyanto; Jeremiah Batista Hutagaol; Moch. Annas Hidayatulloh (Future Science, 2023)
The effectiveness of the system of public education in a country is one of the most important aspects of its development. The COVID-19 initiative affected the educational system previously. The education system in Indonesia, however, is utilizing the offline or non-network learning approach now that the COVID-19 pandemic conditions, particularly in Indonesia, have abated. The teaching and learning process that takes place in schools exposes pupils to issues that develop in the educational setting and are frequently experienced by students. The frequent occurrence of saturation and exhaustion during school activities is one example. The objective of this final project is to determine the level of saturation and fatigue in offline learning among students at ABC Elementary School and to propose improvements to minimize the levels of saturation and fatigue. The methods used for research are MBI-SS (Maslach Burnout Inventory-Student Survey) for the level of saturation and SOFI (Swedish Occupational Fatigue Inventory) for the level of fatigue. The research results from 75 students show that for the level of saturation, there are 49 students (65%) in the low category, 25 students (34%) in the moderate category, and 1 student (1%) in the high category. For the level of fatigue, there are 56 students (75%) in the moderate category, 19 students (25%) in the moderate category, and 0% in the high category. To saturation and fatigue, the school can engage in ice-breaking activities, inject humor during learning sessions, and provide additional nutrition such as pudding or similar items in the morning.